Enhancement of Seeding and Electroless Cu Plating on TaN Barrier Layers: The Role of Plasma Functionalized Self-Assembled Monolayers. Issue 9 (1st January 2016) - Chen, Giin-Shan; Wu, Ding-Ye; Chen, Sung-Te; Cheng, Yi-Lung; Fang, Jau-Shiung; Yang, Tzu-Ming
Abstract : Self-assembled monolayers (SAMs) are extensively used in microelectronic copper metallization primarily as seed-trapping layers, diffusion barriers, or pore-sealants for porous dielectric materials. However, direct electroless copper plating of nitride barrier layers assisted by a seed-trapping SAM is rarely examined. Therefore, this work uses TaN, a standard barrier material for Cu metallization, as a model substrate to develop a new seeding (catalyst formation) process for electroless copper plating, involving substrate pretreatments from piranha etching (hydroxylation), octadecyltrichlorosilane SAM (OTS-SAM) deposition and subsequent functionalization. Catalytic particles upon adsorption onto piranha-treated (reference) TaN layers via Ta−OH linkages tend to agglomerate to give a limited density of 8 × 10 13 m −2 . In contrast, those adsorbed on piranha-treated TaN layers with a plasma-functionalized OTS-SAM over-coating are free from agglomeration and remain an average size of only 3 nm, along with an elevated density of 1 × 10 15 m −2 . X-ray photoelectron spectroscopy, together with transmission electron microscopy, clearly identifies the thin-film materials deposited and functional groups induced by each of the pretreatments, allowing the mechanism of seeding enhancement to be clarified. Finally, the enhancement of seeding to benefit electroless copper plating will be demonstrated.